The Ability of Vocational High School Teachers to Developing HOTS Question - Anas Arfandi; Hamidah Suryani; Nurhaedah Nurhaedah; Panennungi Panennungi; Onesimus Sampebua (Three E Science Institute, 2021)
The purposes of this study are to 1) describe the form of the question made by vocational school teachers, 2) elaborate the teacher's method in preparing questions to evaluate the learning outcomes, 3) explain the teacher's comprehension in preparing questions that measure high order thinking skills, and 4) analyze the teacher's skills in preparing questions that measure high order thinking skills. The research is descriptive and correlational. The population and sample of this research are productive vocational high school teachers who teach at the Technical of Construction and Property expertise program in the province of South Sulawesi. Data collection was carried out in March – June 2021. Determination of the samples used the Slovin formula with an error rate of 0.05. The sample used is 59 respondents. Analysis of research data using descriptive statistics and cross-tabulation. The results of the study show that 1) the form of questions combines an objective test and a subjective test. 2) the preparation of examination questions is preceded by making a question grid, then dividing the categories of questions based on their cognitive level. 3) Dominant teachers have understood the preparation of questions that measure high-level thinking skills, however, almost 40% of teachers still need further strengthening. 4) Dominant teachers have been skilled in preparing HOTS questions, however, there are still 20% of teachers who still need assistance in preparing High-Order Thinking Skills (HOTS) questions. 5) Teachers with 11-20 years of service are more dominantly skilled at preparing HOTS questions.